DETERMINATION OF FIRM VALUE: THE ROLE OF FINANCIAL FLEXIBILITY, FIRM SIZE, AND CAPITAL STRUCTURE IN FOOD AND BEVERAGE ISSUERS LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) - Ni Putu Gita Mahayani; Ida Ayu Agung Idawati; Ni Nyoman Suriani (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2026)
A company's value is an important indicator that reflects performance and influences investor interest. This study aims to examine the influence of financial flexibility, firm size, and capital structure on the value of companies in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) during 2021-2023. The purposive sampling method was used to select 10 companies as a sample, and the data obtained from the annual reports as well as financial statements were statistically analyzed to determine the significance and direction of influence of the variables. The results show that the size of the company has a positive and significant effect on the value of the company; financial flexibility shows a non-significant negative influence; and capital structure has a positive influence that is also not significant. The study's conclusion is that while firm size plays an important role in increasing a company's value, financial flexibility and capital structure may not have a major impact. This research enriches understanding of financial management practices in the emerging market food and beverage sector and offers valuable insights for stakeholders in investment decision-making.